Řízení nákladů v podniku - Havlová, Petra (Vysoké učení technické v Brně. Fakulta podnikatelská, 2018)
Cílem diplomové práce je popsat a zanalyzovat současný stav řízení nákladů a navrhnout opatření pro zlepšení stavu. Teoretická část je věnována klasifikaci nákladů, kalkulacím a nástrojům pro řízení nákladů. Praktická část pak popisuje řízení nákladů v analyzované firmě. Dále je provedena vertikální a horizontální finanční analýza. Z analýz řízení nákladů jsou nadefinována opatření pro zlepšení stavu. Z vertikální a horizontální analýzy vyplynuly nákladové položky, kterým je vhodné věnovat pozornost.

The aim of the thesis, which is divided into a theoretical and a practical part, is to describe and analyze the current tendency in a company’s cost management, and suggest a precaution leading to an improvement. The theoretical part compiles the classification of costs, calculations, and tools and processes of cost management. The practical part then describes cost management in the analyzed company. Both vertical and horizontal financial analysis are rendered – from the analyses, precautions are defined, as well as cost items, which are suggested to be paid attention to.
Cost Controlling in a Company
Keywords: Řízení nákladů; Kalkulace; Technicko-hospodářské normy; ABC metoda; Cost management; Calculation; Techno-economic standard; Activity Based Costing